Investigations of Phytochemical, Analgesic, Anti-Inflammatory and Antipyretic Effects of Ixora Pavetta Andrews Leaf - Latif Najmi, Shafaq Rafiq, Syed Hyder Raza, Gul-E-Nazish, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The aim of this study was to evaluate the effect of ethanol extract of I.pavetta Andrews leaf on acute toxicity, anti-inflammation, antipyretic and analgesic effect in albino rats. Methodology: The plant leaves I.pavetta were taken and obtained materials were washed, shade dried into coarse powder using a mechanical grinder and then to prepare ethanol extract. The different phytochemical compounds such as alkaloids, saponins, glycosides and tannins were present in the ethanol extracts. The total number of rats was 30 which included male and female albino rats. The age range was 160-240g. All data was analyzed by SPSS 21. Results: The results indicated that the extract's LD50 is greater than 3000 mg/kg, p.o., and that no mortality was seen at this dose for 14 days. In terms of analgesic activity, the use of different doses of ethanol extract (600, 800mg/kg) show significantly reduced; p<0.0001*** the number of writhes and caused the highest analgesic effect than compared to the reference drug group (Aspirin 100mg/kg). The carrageenan induced hind-paw oedema in rats were used to explore the anti-inflammatory effects, and the study's findings showed that the use of different dose of extract at (600 and 800 mg/kg) had shown significantly; p<0.001** reduced inflammatory and pain effects in rats as compared to reference drug (phenylbutazone 100mg/kg). The yeast-induced pyrexia in rats was used to test the antipyretic efficacy, and the different dose of extract significantly; p<0.001** decreased body temperature at doses of (600 and 800 mg/kg) than compared to the acetylsalicylic acid (100mg/kg). Conclusions: The ethanol extract of plant leaf I. pavetta have shown greater analgesic efficacy, anti-inflammation and antipyretic activities. Keywords: Acetic acid, analgesic effect, anti-inflammation.